2016
DOI: 10.1667/rr14374.1
|View full text |Cite|
|
Sign up to set email alerts
|

PIDD Mediates Radiation-Induced Microglia Activation

Abstract: Radiation-induced brain injury (RIBI) is the most common adverse effect that occurs after cranial radiation therapy (CRT). We have previously reported that CRT-induced release of pro-inflammatory cytokines in brain tissues and inhibition of neurogenesis in the hippocampus might be caused by microglial activation and may play an important role in RIBI. In this study we examined the role of p53-induced protein with a death domain (PIDD) in radiation-induced activation of BV-2 cells. BV-2 cells were transfected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…The NF-κβ pathway plays a vital role in supporting the initiation and progression of tumor cells and resistance to radiation. 24 A previous study 25 showed that the most common adverse reaction that occurs after craniocerebral radiotherapy (CRT) is radiation–induced brain injury (RIBI), and the release of pro-inflammatory cytokines and the activation of microglia in brain tissue induced by CRT played important roles in RIBI. This study also indicates that silencing PIDD (p53-induced protein with a death domain) expression can inhibit the transcriptional activation of microglia by down-regulating the PIDD-C/NF-κβ pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The NF-κβ pathway plays a vital role in supporting the initiation and progression of tumor cells and resistance to radiation. 24 A previous study 25 showed that the most common adverse reaction that occurs after craniocerebral radiotherapy (CRT) is radiation–induced brain injury (RIBI), and the release of pro-inflammatory cytokines and the activation of microglia in brain tissue induced by CRT played important roles in RIBI. This study also indicates that silencing PIDD (p53-induced protein with a death domain) expression can inhibit the transcriptional activation of microglia by down-regulating the PIDD-C/NF-κβ pathway.…”
Section: Discussionmentioning
confidence: 99%
“…miR-135b-5p overexpression can significantly alleviate hippocampus neuron damage and oxidative stress [ 55 ], and miR-135b-5p can also be a diagnostic marker for mild craniocerebral injury during exercise [ 56 ]. Moreover, studies have also confirmed that Pidd, a critical switch between NF-κB- and radiation-induced apoptosis, can regulate microglial activation induced by radiation [ 57 ]. In contrast, Pidd silencing can inhibit NF-κB activation and reduce inflammation, as inflammation can activate the microglia [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cranial irradiation reduced CD206 expression and increased IL1-beta expression in the mouse brain associated with the absence of monocyte-derived macrophages and long-lasting inflammation ( 52 ). Irradiation-induced release of pro-inflammatory cytokines in brain tissue microglial activation might be caused by microglial activation and is mediated by the PIDD-C/NF-κβ transcription pathway ( 53 ). In common, these data reveal immune component of brain TME as potential theraupeutic targets for combined immunotherapy and radiotherapy to treat GBM patients.…”
Section: Discussionmentioning
confidence: 99%